Analisis Kemampuan Teknik Dasar Passing Bawah Permainan Bola Voli pada Peserta Ekstrakurikuler SD Negeri 63 Lubuklinggau - Yandhi Noer Permadhi; Leo Charlie; Hengki Remora (Yayasan Darussalam Bengkulu, 2025)
This study aims to determine the Underhand Passing Technique Ability in Volleyball Games on Extracurricular Participants of SD Negeri 63 Lubuklinggau City. This study is a qualitative descriptive study that explains the situation or activities that are taking place by triangulating data. In this study, the population was 15 people and a sample of 15 people participated in volleyball training activities at the Extracurricular SD Negeri 63 Lubuklinggau. Data collection techniques used observation and interviews to determine the abilities of each individual. The results of this study indicate that the description of the ability of the underhand passing technique in the Extracurricular Participants of Elementary School 63 shows results that are in accordance with the data obtained by the researcher, seen from the preparation attitude, the attitude of contact and the ending attitude based on the results of observations, interviews, and documentation. The conclusion in this study is that some players still have difficulty in the attitude of contact, but for the ability of elementary school volleyball players, the ability of underhand passing is good